Advancing policy development for vertical agrivoltaics: Research on landscape integration and social acceptance - Biró-Varga, Kitti; Stremke, Sven (Renewable energy, 2026)
Agrivoltaic systems, combining agriculture with solar energy generation, are gaining wide international popularity. Recent developments include the upscaling of vertical interspace systems that integrate bifacial solar modules with livestock grazing or arable farming. In the Netherlands, peat reclamation landscapes have significant potential for accommodating these systems due to their extent and parcellation structure. This study explores that potential through a case study in the province of Gelderland. A methodology is developed to articulate principles and guidelines for the landscape-inclusive development of vertical agrivoltaics, which, in turn, provide the foundations for spatial policies in low-lying landscapes. Design guidelines are devised based on a literature study and visualised for an online survey conducted with experts. The survey helped to determine whether the proposed guidelines can maintain the landscape quality of the selected sites. The results show that promoting accessibility and including park-like functions in agrivoltaics improve landscape quality, as well as incorporating measures for biodiversity and wildlife habitats. The visual appearance and shielding of agrivoltaics also represent an important topic in literature and policy recommendations. The methodology, design guidelines and policy recommendations are relevant for similar open landscapes in the Netherlands and elsewhere.